Etiology and Pathogenesis of Unicystic Ameloblastoma Based on The Histopathology Examination Result Analysis - Harianto, Azzah Aqillah; Hardianto, Andri; Hadikrishna, Indra (Indonesian Dental Association, 2024)
Unicystic ameloblastoma is a type of ameloblastoma that often occurs at a young age. Unicystic ameloblastoma can occur due to neoplastic transformation from an odontogenic cyst to an odontogenic tumor, ameloblastic transformation of reduced enamel epithelium from developing teeth, or cystic degeneration of solid ameloblastoma. However, there is no convincing evidence has yet been found for each proposed pathogenesis. This study aims to determine the development of etiology and pathogenesis of unicystic ameloblastoma based on the analysis of the results of histopathological examination. This study aims to determine the development of etiology and pathogenesis of unicystic ameloblastoma based on the analysis of the results of histopathological examination. The study was conducted using a systematic review method through searching journals on PubMed, Google Scholar and Scopus using keywords. In the initial search, 1109 journals were obtained, which were then selected based on inclusion criteria, namely English-language journals published in 2017-2020, indexed in Scopus, and relating to the etiology and pathogenesis of unicystic ameloblastoma based on the analysis of the results of histopathological examination, so that 16 journals were obtained. Etiology of the unicystic ameloblastoma has not undergone renewal, and the currently known pathogenesis of the unicystic ameloblastoma is molecular pathogenesis, namely where the development of odontogenic lesions occurs due to pathogenic gene mutations that affect the signaling pathway. The mutation that often occurs is the BRAF V600E mutation which is included in the MAPK signaling pathway.